Enhancing Holistic Care of Patients with Obstetric Fistula and Other Childbirth Injuries -TERREWODE’s Experience of Developing a Dedicated Fistula Hospital in Uganda - Emasu, Alice; Andrews, Martin; Ruder, Bonnie; Barageine, Justus K (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To document experiences of establishing state of the art women’s hospital offering holistic care to women with obstetric fistula and other child birth injuries. The care includes comprehensive treatment and management of the affected women, reintegration services that support the restoration of women’s dignity and clinical for prevention Methods: TERREWODE Women’s Community Hospital (TWCH) founded in 2016 is a subsidiary of The Association for Rehabilitation and Re-Orientation of Women for Development (TERREWODE), a Ugandan Non-Government Organization. We received, funding and support from International Fistula Alliance ,Ugandan Fistula Fund for TERREWODE, Catherine Hamlin Fistula Foundation, Hamlin Fistula USA and Hamlin Fistula Ethiopia. Results: The first phase has a 30-bed fistula surgical block and 30-bed rehabilitation and reintegration center, in addition to administration, catering and support facilities. This community-focused hospital will provide holistic routine care to patients with obstetric fistula and other childbirth injuries. It will also conduct: health education, research, Continuous Professional Development, patient rehabilitation and reintegration. On completion other services will include: conducting deliveries, neonatal care, and Antenatal care and family planning services. Up to 600 surgeries annually will be conducted in the unit. This will decongest public health facilities and reduce current backlog. Our critical success factors include: ability to attract and retain highly qualified and self-motivated personnel; our relationship with key stakeholders including Ministry of Health, suppliers, development partners and our target beneficiaries. Conclusions: It is possible with collaboration to establish specialized units offering quality care to women with birth trauma. Our experience can be replicated in other settings.